2016
DOI: 10.1242/dev.139907
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling via Axin2 is required for myogenesis and, together with YAP/Taz and Tead1, active in IIa/IIx muscle fibers

Abstract: Canonical Wnt/β-catenin signaling plays an important role in myogenic differentiation, but its physiological role in muscle fibers remains elusive. Here, we studied activation of Wnt/β-catenin signaling in adult muscle fibers and muscle stem cells in an Axin2 reporter mouse. Axin2 is a negative regulator and a target of Wnt/β-catenin signaling. In adult muscle fibers, Wnt/β-catenin signaling is only detectable in a subset of fast fibers that have a significantly smaller diameter than other fast fibers. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 49 publications
(79 reference statements)
1
54
0
Order By: Relevance
“…As considering the Wnt as a profibrotic factor, Majidinia and Yousefi () reported that a continued increase in activity of the canonical Wnt signaling pathway in myogenic progenitors is related to enhance in the differentiation of myogenic satellite cells to fibrogenic lineages in aging mice. Huraskin et al () also reported the same resulted and showed that upon injury, Wnt/β‐catenin signaling was detected in muscle fibers with centrally located nuclei. Another tissue with successful regulation after injuries induced by drug or alcohol toxicity and persistent viral infection is liver.…”
Section: Wnt/β‐catenin Signaling In Regenerative Medicinementioning
confidence: 73%
“…As considering the Wnt as a profibrotic factor, Majidinia and Yousefi () reported that a continued increase in activity of the canonical Wnt signaling pathway in myogenic progenitors is related to enhance in the differentiation of myogenic satellite cells to fibrogenic lineages in aging mice. Huraskin et al () also reported the same resulted and showed that upon injury, Wnt/β‐catenin signaling was detected in muscle fibers with centrally located nuclei. Another tissue with successful regulation after injuries induced by drug or alcohol toxicity and persistent viral infection is liver.…”
Section: Wnt/β‐catenin Signaling In Regenerative Medicinementioning
confidence: 73%
“…Canonical Wnt signaling activates TEAD1 and Hippo transducer YAP1 in myoblast proliferation and differentiation (Huraskin et al, 2016). As WISP1 is a downstream target of Wnt signaling, we studied whether WISP1 regulates YAP1/TEAD1 activation.…”
Section: Wisp1 Upregulated Glut1 Expression Via Yap1/tead1mentioning
confidence: 99%
“…However, cooperation between the pathways consistent with the Piccolo model has been described during chronic inflammation-induced metaplasia in corneal epithelium 53 . In addition, Wnt3a activates both TCF and TEAD reporters in skeletal muscle cells 54 . Adding to the mechanistic insight linking YAP and β-cat, SET domain-containing lysine methyltransferase 7 (SETD7) is present in the destruction complex and methylates YAP, which is required for its ability to promote the nuclear accumulation of β-cat 55 .…”
Section: Updates To the Standard Model Of Wnt Gene Regulationmentioning
confidence: 99%